(untitled) (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: The article is devoted to the features of the material composition of bitumen from its occurrence in the Orenburg Cis-Urals region. In the course of the study the patterns of distribution of metals, including noble ones, in the oil and gas fields of the Orenburg part of the Volga-Ural oil and gas province, bitumen samples from various areas and deposits of the platform Orenburg region were also studied. The solid black rock sample containing bitumen found in the Cis-Ural trough was of particular interest. The purpose of this study was investigation of the material composition of the solid black rock sample containing bitumen, found in the Orenburg Cis-Urals region. Methods: The material composition of bitumen was studied by X-ray phase and spectral analysis, microscopic methods, and Raman spectroscopy. Results and discussion: According to microscopic methods, the sample was a black fragmented rock with bitumen and mineral inclusions of predominantly carbonate composition. Bitumen also contained fragments of quartz, euhedral quartz crystals, and fine-grained quartz rock. According to powder X-ray data, the mineral component of bitumen was represented by a mixture of dolomite, calcite, and quartz. The presence of carbonaceous matter of varying degrees of metamorphism (from weakly altered organic matter to anthracite-like coal) in bitumen was detected by Raman spectroscopy. The determination of metals in bitumen was performed by spectral analysis. The contents of the detected metals were compared with the clarks of these metals in carbonate rocks. Comparative analysis showed elevated contents of the following metals: Cu, Pb, Ni, Co, Cr, Mo, Sn, Be, Ag, Ga, Ba, Zn, Mn, Sc, La, Nb. Conclusions: The mineral composition of natural bitumen was represented mainly by dolomite, calcite, and quartz. This bitumen also contained various forms of carbonaceous matter - carbonaceous matter of varying degrees of metamorphism. Elevated contents of the following metals have been established in bitumen compared to the average contents of these metals in carbonate rocks: Co, Nb, Cu, Be, Ba, Zr, Ag, Mn, and others.